IMPLEMENTATION OF THE PEDAGOGICAL TECHNOLOGY OF PROFESSIONAL-PERSONAL ECOLOGICAL EDUCATION IN TECHNICAL UT - Savriyeva Iqbol Bahodirovna, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
In this article, the acquisition of ecological knowledge and skills for professional activity, the acquisition of practical knowledge of ecology and environmental protection, the advantage of laboratory training, the training, education, development, self-education of individuals and the population aimed at the formation of norms of behavior and special knowledge and issues such as the experience-gathering process, aspects of laboratory practicum design, practice-oriented training stages, population ecology and pedagogical technology of professional-personal ecological education in technical higher education institutions are highlighted.